A história e a língua na mídia escrita no Brasil na década de 1960 - Luciano Junior, Cillas (2007)
This dissertation is a historical- historiographic study about the use of the Portuguese Language during the period of the Military Regime in Brazil, in the Sixties. The material for analysis is focused on the period that dates from 1960 to 1970, more specifically on the day that the nation celebrates the anniversary of its Independence held annually on September 7th. By following the guidelines of the theory proposed by Konrad Koerner (1995,1996), which is supported by three (3) well-defined principles, we shall identify, in the documents, the marks which feature the aspects of the censorship over print media. During this research, we have noticed that the 60 s decade was a period regarded for some remarkable social events in History, Politics and Culture. In that context, we have the ascension of the Military Regime and the establishment of a new government, imposing the censorship over mass media, such as newspapers, radio, television and broadcasting. At this portion of History, it s verified a significant development of the print media, especially, when we think in its strength of influence and its role as a source of information and opinionmaker. The analysis of the selected documents allowed us to realize the language as a social issue, as well, the strength of the historical context from that time, whereas the documents materialize a sort of attitudes directly related to the Brazilian Government and to the celebrations of Brazil s Independence Day, as a manner to promote the State and the civic values